Effect of plant remains on abrasive wear rate of the tilling machine movable operating parts - Borak, K.V. (Problems of Tribology, 2020)
Abrasive wear is one of the most common types of wear accounting for up to 50% of all failures of machine parts. The study of laws governing the process of abrasive wear process is undoubtedly a critical task. The paper is dedicated to the effect that the chemical factor, in particular the presence of plant remains in the abrasive mass, has on the tilling machine movable operating parts abrasive wear rate. Laboratory researches were performed with the Impeller technique, while the field tests – with a multipurpose disk tiller UDA-4.5 in the conditions of the Ovruch district of Zhytomyr region (sandy loam soil). As follows from the study, the ooze of the sap (syrup) leads to an increase of the abrasive wear rate by 13.5… 21.5% in the laboratory conditions and by 8% in the field conditions. Results of the field tests confirm those of the laboratory studies, although the latter have demonstrated an increase in the wear rate, which is by 13.5% greater than got upon the field tests. Such a deviation is conditioned by a higher concentration of the corn crop remains in the abrasive mass during laboratory testing. Abrasive wear of the tilling machine movable operating parts may not be identified as a simple mechanical process, as the working surface wear rate may be significantly increased by the chemical factor when subject to wear in the real soil